Effectiveness of oral rotavirus vaccination in England against rotavirus-confirmed and all-cause acute gastroenteritis. (11th April 2019) - Walker, Jemma L.; Andrews, Nick J.; Atchison, Christina J.; Collins, Sarah; Allen, David J.; Ramsay, Mary E.; Ladhani, Shamez N.; Thomas, Sara L.
Highlights: Rotarix® had very good vaccine effectiveness (VE) in UK public health use. Two-dose VE against confirmed infection in young children was 77% (95%CI:66–85%) The vaccine programme was exceptionally successful (>90% vaccine uptake, high VE) Thus, it is highly likely that most acute gastroenteritis (AGE) was no longer due to rotavirus. This explains the lack of demonstrable VE against all-cause AGE. Abstract: Background: The monovalent oral rotavirus vaccine Rotarix® was introduced into the UK infant immunisation programme in 2013. We estimated vaccine effectiveness (VE) in the first two years of the programme. Methods: We used a test-negative case-control design and enhanced national surveillance data for 1869 vaccine-eligible children tested for rotavirus infection to obtain adjusted odds ratios and VE against laboratory-confirmed rotavirus infections. Linked anonymised UK primary care and hospitalisation data from the Clinical Practice Research Datalink (40, 723 children) and random-effects Poisson regression were used in a cohort study to estimate VE against all-cause acute gastroenteritis (AGE) and AGE hospitalisations. Results: VE against laboratory-confirmed infection was 69% (95% Confidence Interval: 40–84%) for one dose and 77% (95%CI: 66–85%) for two doses. Two-dose VE in children aged <12 months and ≥12 months was 85% (95%CI: 74–91%) and 54% (95%CI: 15–75%), respectively. In contrast, we found no evidence that the vaccine was effective against all-cause AGE (VE = −20%, 95%CI: −36% to −5%), or against AGE hospitalisations (VE = 35%, 95% CI: −86% to 77%). Conclusions: In this first detailed assessment of VE of the Rotarix® vaccine in the English national programme, we show that Rotarix® was highly effective in preventing laboratory-confirmed rotavirus infection in young children. This provides reassurance about the vaccine's performance in real-life settings and gives key information for future cost-effectiveness analyses. The high VE against rotavirus-specific AGE, and the exceptionally successful implementation of the national rotavirus vaccine programme (with >90% vaccine coverage), explains the lack of VE against all-cause AGE because most AGE in the post-vaccine era would not have been due to rotavirus, although some underestimation of VE could also have occurred due to differential healthcare utilisation by vaccinated and unvaccinated infants. This highlights the importance of using specific vaccine-preventable endpoints for these scenarios.